2012
DOI: 10.3390/ijerph9051715
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Traffic Activity on Heavy Metal Concentrations of Roadside Farmland Soil in Mountainous Areas

Abstract: Emission of heavy metals from traffic activities is an important pollution source to roadside farmland ecosystems. However, little previous research has been conducted to investigate heavy metal concentrations of roadside farmland soil in mountainous areas. Owing to more complex roadside environments and more intense driving conditions on mountainous highways, heavy metal accumulation and distribution patterns in farmland soil due to traffic activity could be different from those on plain highways. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 37 publications
5
76
3
Order By: Relevance
“…Therefore, a further roadside study is needed to investigate these metals’ distribution to identify how far these contaminants can actually reach. However, Zhang et al [9] reported that the exponentially decreasing distribution pattern was not available in farm land soil due to agricultural activities and mixed metal resources. In the Qinghai-Tibet Plateau, the industrial facilities are very limited and its fossil fuel consumption is relatively low [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a further roadside study is needed to investigate these metals’ distribution to identify how far these contaminants can actually reach. However, Zhang et al [9] reported that the exponentially decreasing distribution pattern was not available in farm land soil due to agricultural activities and mixed metal resources. In the Qinghai-Tibet Plateau, the industrial facilities are very limited and its fossil fuel consumption is relatively low [30].…”
Section: Resultsmentioning
confidence: 99%
“…However, other research results showed that the special distribution patterns of heavy metals in roadside soils were not always significantly correlated with the roadside distance [3,4,9]. This may be attributed to mixed sources of metals, agricultural activities and roadside green belts [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollutants transferred from the Upper Silesian Industrial Region are deposited in the west while 35 km east of Krakow are deposited contaminants from Krakow, primarily from the steel producer ArcelorMittal Poland Unit in Krakow. According to Zhang et al (2012), wind direction and speed might change the heavy metal contaminants of soil. Ogunkunle and Fatoba (2014) studied the level of soil contamination by Pb, Cu, Cr, Cd and Zn and showed that these heavy metals are deposited at various distances depending on wind velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between Pb and other metals can yield insight into both the source of metal contamination and the mode of transport. In urban soils, a correlation between Pb and Zn has been suggested to be linked with traffic patterns and the combustion of leaded gasoline (Mielke et al, 1983;Zhang et al, 2012) while associations between Pb and Ti have been linked with Pb-based paint contamination (Clark et al, 2006). Within the municipally sourced matrix, the Pb/Ti ratio systematically varies, nearly linearly, when plotted against the major element ratio (Si/Ca).…”
Section: Trace Element Geochemistrymentioning
confidence: 99%